KASUS TINDAK PIDANA PEMBUHUHAN (ABORSI): TINJAUAN YURIDIS DAN FILOSOFIS - Budoyo, Sapto; Sutono, Agus; Arofah, Nilna Nur (FPIPSKR Universitas PGRI Semarang, 2023)
Abortion is one of the causes of death of women in childbearing years in developing countries which is done secretly and usually by personnel who are not specifically educated, including pregnant women who want action. philosophically against the crime of murder, abortion, Indonesian criminal law in the judge's decision Number 252K/Pid/2017. The method used in this research is normative juridical, namely an approach that is carried out based on the main legal material by examining theories, concepts, legal principles, and legislation related to qualitative descriptive approach research, with data collection from the study. literature. The results of this study conclude that the sanctions for the perpetrators of the crime of abortion in article 346 of the Criminal Code with a maximum imprisonment of four years in prison. The sanctions for perpetrators of the crime of abortion in the Criminal Code (KUHP) strictly prohibit abortion for any reason, while the Health Law allows abortion on medical indications or because of rape